The relation between cerebral small vessel function and white matter microstructure in monogenic and sporadic small vessel disease - the ZOOM@SVDs study - Naomi Vlegels; Hilde van den Brink; Anna Kopczak; Tine Arts; Stanley D.T. Pham; Jeroen C.W. Siero; Benno Gesierich; Alberto De Luca; Marco Duering; Jaco J.M. Zwanenburg; Martin Dichgans; Geert Jan Biessels (Cerebral Circulation - Cognition and Behavior)
In cerebral small vessel disease (cSVD), vascular dysfunction has been associated with cSVD-lesions across the brain. Here we further explore the relation between vascular dysfunction and cSVD-related brain injury. We tested two hypotheses: (1) that complementary measures of abnormal small vessel function relate to decreased white matter integrity, and (2) that local variance in vascular dysfunction relates to local variance in white matter integrity within individual patients.We included 23 patients with monogenic cSVD (i.e. CADASIL) and 46 patients with sporadic cSVD. With whole-brain analyses, we tested if small vessel flow velocity and reactivity measures from 7T-MRI were associated with global peak-width-of-skeletonized-mean-diffusivity (PSMD). We also tested voxel-wise correlations between reactivity to hypercapnia and mean diffusivity (MD) in white matter.Whole-brain analyses showed a negative association between blood flow velocity and PSMD for the perforating arteries in the centrum semiovale in CADASIL (p = 0.04) and in the basal ganglia in sporadic cSVD (p = 0.002). Global white matter reactivity to hypercapnia was not associated with PSMD. Within patients, both in CADASIL and sporadic cSVD, we observed significant voxel-wise negative correlations for endothelial-independent vascular reactivity and MD in the white matter.These findings confirm our hypothesis that small vessel dysfunction in patients with cSVD is associated with microstructural white matter alterations, also at voxel level. The latter may reflect a direct relationship between local small vessel dysfunction and tissue injury.